Effect of incorporating wing veins on soft wings for flapping micro air vehicles - Ishiguro, Risa; Kawasetsu, Takumi; Hosoda, Koh (Frontiers in Robotics and AI, 2023)
Small insects with flapping wings, such as bees and flies, have flexible wings with veins, and their compliant motion enhances flight efficiency and robustness. This study investigated the effects of integrating wing veins into soft wings for micro-flapping aerial vehicles. Prototypes of soft wings, featuring various wing areas and vein patterns in both the wing-chord and wing-span directions, were fabricated and evaluated to determine the force generated through flapping. The results indicated that the force is not solely dependent upon the wing area and is influenced by the wing vein pattern. Wings incorporating wing-chord veins produced more force compared to those with wing-span veins. In contrast, when the wing area was the specific wing area, wings with crossed wing veins, comprising both wing-span veins and wing-chord veins, produced more force. Although wing-chord veins tended to exert more influence on the force generated than the wing-span veins, the findings suggested that a combination of wing-span and wing-chord veins may be requisite, depending upon the wing area.